Estudio de prefactibilidad para la instalación de un centro de hemodiálisis - Velásquez Rivera, Carlos Javier (2020)
Currently, kidney failure is a disease that occurs when the kidneys suddenly lose the ability to filter waste from the blood. When this occurs, harmful levels of waste can accumulate and there may be an imbalance in the chemical composition of the blood. There are two types of renal failure: acute and chronic. In the case of chronic renal failure, this leads to a dialysis program to cope with this disease. Given this problem, an alternative is presented for patients with chronic renal failure: the installation of a hemodialysis center. In this way, it is sought to provide the service to patients with social insurance and who need to be dialyzed, this service will be covered by EsSalud in its entirety and the patients will be evaluated and attended by the hemodialysis center assistance staff. Hemodialysis is a medical treatment that artificially removes harmful or toxic substances from the blood using a hemodialysis machine. For this, patients have previously placed a fistula or catheter through which they are connected to the machine. This treatment is performed three times a week in patients in stage 5 (terminal phase) and the duration of each session is three to four hours, depending on the amount of fluid to be extracted to the patient. For all the above, the installation of a hemodialysis center as a treatment for patients with chronic renal failure would help to improve the patient´s quality of life, generate employment, motivate them to investigate kidney failure and chronic diseases, encourage new doctors to specialize in nephrology and the state to encourage the creation of more dialysis centers since about 300 centers are currently needed and only have 140.